Quantificação de carbamato de etila em vinhos - Picoli, Paula Monique Chiconi de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The ethyl carbamate is a compound present in most foods yeast-distillates; due to its carcinogenic potential, national legislation has established a limit of 0.150 µg / mL for spirits, so the values above the same, pose a threat to both public health as well for the economic sector by preventing the export of these products. The aim of this work is to provide the optimization of an analytical method employing the technique of gas chromatography equipped with flame ionization detector (FID) to determine the concentration levels of ethyl carbamate in some samples of wine. The use of ethyl acetate as solvent employed in the extraction, the ethyl carbamate present in wine samples proved to be suitable, where Recoveries were between 97.6 to 103.3% (m / m), with a standard deviation for between 0.56 to 3.50%. The concentrations of ethyl carbamate in particular wine samples vary between 3.22 µg / ml and 3.80 µg / mL, with a mean of 3.48 µg / mL. These valuesare all above the limit set by law. Thus, the results indicate the need for changes in the process of wine production, in order to control the levels of the substance

O carbamato de etila é um composto presente na maioria dos alimentos fermento-destilados; devido ao seu potencial carcinogênico, a legislação nacional estabeleceu um limite de 0,150 μg/mL para bebidas destiladas, valores superiores ao mesmo representa uma ameaça tanto para saúde pública como também para o setor econômico, já que impedem a exportação destes produtos.Objetivou-se neste trabalho efetuar a otimização de um método analítico empregando a técnica de cromatografia gasosa equipado com o detector deionização de chama (FID), para determinar os níveis de concentração de carbamato de etila em amostras de vinhos. O emprego do acetato de etila como solvente empregado na extração, do carbamato de etila presente em amostras de vinhos, mostrou-se adequado, onde foram obtidas recuperações entre 97,6 a 103,3 % (m/m), com um desvio padrão relativo entre 0,56 a 3,50%. Os níveis de concentração de carbamato de etila determinados emamostrasde vinhosvariam entre 3,22 μg/mL e 3,80μg/mL, com média de 3,48 μg/mL. Estesvalores são bem superiores ao limite estabelecido pela legislação. Desta forma os resultados indicam a necessidade de alterações no processo de produção de vinho, visando o controle dos teores da substância
Keywords: Vinho e vinificação - Química; Vinho e vinificação - Analise; Bebidas destiladas; Saúde pública; Cromatografia a gás; Bebidas alcoolicas - Sabor e aroma; Wine and wine making - Chemistry